Compliance With Mandatory Employee Stock Option Disclosure and Its Relationship With Corporate Governance Characteristic - Mazlina, Abdul Majid (2011)
This study examines the association of corporate governance characteristic in employee stock option (ESO) disclosure in Malaysian annual reports. The study is motivated by the limited studies on ESO disclosure in Malaysia compare to other countries. Disclosure is examined in the context of compliance with Companies Act 1965 and Financial Reporting Standard (FRS) 2 - Share-based Payment. Compliance is measured using disclosure index and therefore is discussed in terms of the level of compliance. There are two research questions addressed: 1) what is the nature of compliance with ESO disclosure in company annual report in Malaysia?, and 2) Do corporate governance characteristics influence the compliance of ESO disclosure in company annual report in Malaysia?. It is predicted that internal governance characteristic including board of director effectiveness, audit committee effectiveness and the existence of remuneration committee are associated with the level of compliance with ESO disclosure in the company. 39 sarr~ples had been chosen in this study from the Bursa Malaysia listing which offer ESO plan to their employees. There are two methods of analysis use in this study which are chi-square test and regression analysis. The result from regression analysis indicates that only audit committee size significant but has weak association with the level of ESO disclosure.